Bolanyo - Read, Opie Percival, 1852-1939; Browne, Charles Francis, 1859-1920; Parrish, Maxfield, 1870-1966 (Salt Lake City, UT : Project Gutenberg, 2012)
"Bolanyo" by Opie Percival Read is a novel written in the late 19th century. The story follows the journey of Maurice Belford, a struggling actor from the National Dramatic Company, who finds himself amidst personal and professional turmoil following a disastrous performance and a tragic steamboat explosion. The narrative delves into themes of ambition, camaraderie, and the complexities of artistic expression, all rooted in the rich tapestry of Southern life. The opening of "Bolanyo" introduces us to Maurice Belford as he reflects on his acting career after closing a show in New Orleans. Faced with the harsh criticism of his performance and feeling the strain of competition within his acting troupe, he grapples with issues of self-worth and artistic integrity. After the explosion thrusts him into the river, the story transitions to his recovery, where he meets key figures including Senator Talcom and Mrs. Estell, hinting at deeper personal entanglements and ambitions yet to unfold. This setup establishes not only the protagonist's struggles but also the vibrant world of Bolanyo, setting the stage for explorations of both personal growth and the dynamics of the theatre. (This is an automatically generated summary.)
Release date is 2012-02-10
E-text prepared by Suzanne Shell, Mary Meehan, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Mississippi -- Fiction